Intergenerational Transmission of Maternal Adverse Childhood Experiences on Next Generation’s Development: A Mini-Review - Ishikawa, Keita; Azuma, Natsuko; Ohka, Mai (Frontiers in Psychology, 2022)
Adverse childhood experiences (ACEs) have extremely harmful impacts on an individuals’ physical and mental health throughout their life-span. Recently, it has been reported that maternal ACEs increase the risk of developmental delay in the offspring across generations. This mini review focuses on the direct relationship between maternal ACEs and child developmental delay, and mediators/moderators that associate their relationship. Six studies were identified using three search engines. The results indicated that four out of six studies reported at least one significant direct association between maternal ACEs and child development. Additionally, maternal biological, psychological, and social factors were identified as mediators or moderators. In summary, we identified that maternal ACEs increased the risk of developmental delay in children via biological and psychosocial pathways. Future research should examine potential buffering factors and identify when it is crucial to break the intergenerational transmission.